Building, sustaining and growing: disability inclusion in business. Issue 3 (15th March 2021) - Gould, Robert; Mullin, Courtney; Parker Harris, Sarah; Jones, Robin
Abstract : Purpose: The purpose of this paper is to analyze the unique and the complementary aspects of disability inclusion and diversity strategies and to offer insight for organizations to integrate disability within diversity frameworks. Design/methodology/approach: The research team conducted semi-structured interviews with diversity and inclusion "champions" from large businesses to learn about policies, practices and processes for fostering disability inclusion. The businesses have all received national recognition for supporting employees with disabilities. Findings: Interviewees described strategies to build, sustain and grow disability inclusion by framing disability similarly to other diversity categories. The champions suggested practices to improve disability inclusion initiatives within their organizations. Originality/value: There is limited information on what organizations are doing to support disability inclusion in the workplace. This study builds on the existing literature and responds to calls for case information from business personnel to gather data about common and effective practices.